2018
DOI: 10.1152/ajpcell.00278.2017
|View full text |Cite|
|
Sign up to set email alerts
|

Long noncoding RNA MALAT1 contributes to inflammatory response of microglia following spinal cord injury via the modulation of a miR-199b/IKKβ/NF-κB signaling pathway

Abstract: Long noncoding RNA (lncRNA) metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) was widely recognized to be implicated in human cancer, vascular diseases, and neurological disorders. This study was to explore the role and underlying mechanism of MALAT1 in acute spinal cord injury (ASCI). ASCI models in adult rats were established and demonstrated by a numerical decrease in BBB scores. Expression profile of MALAT1 and miR-199b following ASCI in rats and in vitro was determined using quantitative rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 29 publications
0
64
0
Order By: Relevance
“…In vivo, inflammation markers, including IL‐6, IL‐1β, TNF, and interferon‐γ, were all supressed in MALAT1‐knockout diabetic mice compared to wild‐type mice . Mechanistically, MALAT1 has recently been reported to bind to and modulate NF‐κB activity, thereby regulating the lipopolysaccharide‐induced inflammatory response .…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, inflammation markers, including IL‐6, IL‐1β, TNF, and interferon‐γ, were all supressed in MALAT1‐knockout diabetic mice compared to wild‐type mice . Mechanistically, MALAT1 has recently been reported to bind to and modulate NF‐κB activity, thereby regulating the lipopolysaccharide‐induced inflammatory response .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the rapid development and widespread application of microarray, more and more researchers have found that many lncRNAs are involved in the development of SCI (Shi, Pan, & Feng, ). A recent study found that lncRNA MALAT1 expression was significantly increased (2.4‐fold that of control) in the contusion injured spinal cord of rats, and knockdown of MALAT1 was expected to attenuate SCI through inhibiting inflammatory response of microglial cells (H. J. Zhou et al, ). Furthermore, inhibition of lncRNA Sox2ot expression may protect PC‐12 cells from H 2 O 2 ‐induced injury in SCI by targeting the miR‐211/MCL‐1 isoform2 axis, and the Sox2ot‐miR‐211‐MCL‐1 isoform2 axis may be a promising therapeutic strategy for SCI (Yin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, further study can focus on how lncRNAs interact with immune pathways under pain condition. MALAT1 also contributes to the inflammatory response of microglia following SCI by modulating the miR-199b/IKKβ/NF-κB signaling pathway [68]. In conclusion, MALAT1 is closely related to the inflammatory reaction of microglia cells in a variety of pathological and physiological circumstances, such as brain injury and SCI described above.…”
Section: Altered Expression Of Lncrnas In Biological Np Processmentioning
confidence: 73%